2019
DOI: 10.1177/0300060519863524
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic limbic encephalitis cured with nephron-sparing surgery in a patient with clear cell renal cell carcinoma: a case report

Abstract: Paraneoplastic limbic encephalitis (PLE) in association with clear cell renal cell carcinoma has never been reported in China. We herein describe a 54-year-old man with a 1-week history of headache and a 3-day history of psychiatric symptoms. Slight nuchal rigidity was found by physical examination. Imaging studies of the head were normal. Blood and cerebrospinal fluid antibody testing were both positive for N-methyl-D-aspartic acid antibodies. Subsequent contrast-enhanced computed tomography revealed a 5.2- ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Removing the tumor (usually an ovarian teratoma) is often an important step in the management of anti-NMDA receptor encephalitis [ 46 ]. An article describing a case of anti-NMDAr encephalitis in the setting of clear cell renal carcinoma reported that the patient markedly improved after undergoing nephron-sparing surgery for the tumor [ 47 ]. Another case of a 54-year-old patient with neuropsychiatric symptoms not responding to antiviral treatment for suspected viral encephalitis who had to be sedated due to worsening of his symptoms, was found to have a clear cell renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Removing the tumor (usually an ovarian teratoma) is often an important step in the management of anti-NMDA receptor encephalitis [ 46 ]. An article describing a case of anti-NMDAr encephalitis in the setting of clear cell renal carcinoma reported that the patient markedly improved after undergoing nephron-sparing surgery for the tumor [ 47 ]. Another case of a 54-year-old patient with neuropsychiatric symptoms not responding to antiviral treatment for suspected viral encephalitis who had to be sedated due to worsening of his symptoms, was found to have a clear cell renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…There are no particular clinical patterns, imaging and laboratory abnormalities specific for PNS. In addition, PNS usually occur in patients with lung carcinoma, neuroblastoma or thymoma, but other tumors and malignant lymphomas should be considered as well, as shown in this case [1,[5][6][7][8][9] .…”
Section: Discussionmentioning
confidence: 99%
“…Most neurologic PNS present as peripheral nervous system syndromes and myopathies, as shown in Table 1. Reports on central nervous system presentation are limited to anti-NMDAR and other limbic encephalitis, thus we present the first case of PNS associated with RCC which presented as severe form of Bickerstafflike brainstem encephalitis [2,[9][10][11][12][13][14][15] . Both conditions are antibody-mediated diseases treated with pulse dose methylprednisolone and TPE, which lead to temporal clinical response, as seen in our case.…”
Section: Case Reportmentioning
confidence: 99%
“…Renal cell carcinoma (RCC) is cancer developed from renal cells of several different types according to the cellular origin [ 8 ]. Clear cell is the most common type of RCC, though few case reports of paraneoplastic encephalitis associated with clear cell RCC have been published [ 9 - 11 ]. All aforementioned cases presented with limbic encephalitis, showing memory impairment and cognitive decline without clear lesion on brain magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%
“…RCC have been published [9][10][11]. All aforementioned cases presented with limbic encephalitis, showing memory impairment and cognitive decline without clear lesion on brain magnetic resonance imaging (MRI).…”
mentioning
confidence: 99%